2017
DOI: 10.1108/bjm-04-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Exports-performance relationship in Russian manufacturing companies

Abstract: Purpose The purpose of this paper is to examine the relationship between export activity and firm performance for a positive impact of foreign direct investments (FDIs). The authors also analyze two possible causes of the effect: technology transfer and financial support. The theoretical background is rooted in the resource-based approach taking into account multinational companies’ perspective and the specifics of emerging markets. Design/methodology/approach The authors propose testable hypotheses based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 89 publications
0
10
1
Order By: Relevance
“…Ramstetter (2018) stated the same result on industries in Thailand which showed that the export propensity would be higher for firms that were wholly foreign owned. Bykova & Lopez-Iturriaga (2018) support positive impact of foreign ownership on the link between exports and firms' performance in Russian manufacturing companies. Therefore of the sign of the relationship, the evidence clearly points to the existence of an influence of ownership concentration on a firm's export propensity (Miravitlles et al, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Ramstetter (2018) stated the same result on industries in Thailand which showed that the export propensity would be higher for firms that were wholly foreign owned. Bykova & Lopez-Iturriaga (2018) support positive impact of foreign ownership on the link between exports and firms' performance in Russian manufacturing companies. Therefore of the sign of the relationship, the evidence clearly points to the existence of an influence of ownership concentration on a firm's export propensity (Miravitlles et al, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Although it is a standard indicator in this type of research, it could also have been combined with both financial and non-financial indicators (Sadeghi et al , 2018). Moreover, progress could be made regarding the relationship between exports and firm’s performance (Bykova and Lopez-Iturriaga, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The higher ROA reflects the effective use of assets by enterprises to serve economic benefits for shareholders. Therefore, ROA can reflect many ways on the relationship between corporate governance and firm performance (Al-Matari et al , 2014; Bykova and Lopez-Iturriaga, 2018). Thus, the designated research model for the factors affecting the firm performance of small and medium-sized enterprises in emerging markets, a case of Vietnam, is as follows:…”
Section: Data and Research Methodsmentioning
confidence: 99%
“…Firm size. A company that has a large size will have a large capacity to diversify production and business activities (Bykova and Lopez-Iturriaga, 2018) and implement strategies to increase barriers to potential competitors. At the same time, large-scale enterprises have a lot of power in negotiating prices for the input materials to reduce average costs (Pratheepan, 2014) and improve their profitability and performance (Piao and Moon, 2019).…”
Section: Data and Research Methodsmentioning
confidence: 99%